Pengaruh Berbagai Jenis Pupuk Kandang Dan Frekuensi Penyiangan Terhadap Pertumbuhan Dan Hasil Tanaman Selada Keriting (Lactuca sativaL.) - Oryza Affandina Sani; Hanny Hidayati Nafi’ah; Novriza Satia (JAGROS : Jurnal Agroteknologi dan Sains (Journal of Agrotechnology Science), 2021)
Manure is a fertilizer that is widely used in organic agriculture. The purpose of this study was to determine whether there was a best combination of manure used and weeding frequency on plant growth  and  yields.  The  research  was  done  in Cimaragas, CilawuDistrict, GarutRegency  from August to September 2020. The research used an experimental method with factorial randomized block  design  (FRBD)  consisted  of 2treatment  factors  with 3replications,  namely:  First treatment  (Types  of  Manure)  consisted  of  goat  manure (k1),cow  manure (k2),chicken  manure (k3),and  NPK  fertilizer (k0)as  control.  Second  treatment  (Weeding  frequency)  consisted  of without  weeding (p0),2times  of  weeding (p1),and4times  of  weeding (p2).The  results  showed that  there  was  an  interaction  on  the  observation  parameters  of  dry  weight  and  leaf  area  of  the plant. The combination that gives the best influence was cow manure with 2times of weeding.Keyword: lettuce, manure, weeding